"As Inscrutable as the Sphinx, but Far More Dangerous": Trends in Democratic–Personalist Conflict. Issue 1 (25th February 2023) - Schramm, Madison
Abstract: While liberal democracies do not go to war with other democracies, they frequently engage in conflict with autocratic regimes. Little research has been conducted, however, to indicate what type of autocracies liberal democracies tend to target. This article demonstrates that liberal democracies are more likely to initiate conflict against personalist regimes, rather than autocracies with some form of collective leadership. I argue that, when a conflict of interest arises between a liberal democracy and a personalist regime, liberal foreign policy elites' psychology and social identity work together to produce particular emotional responses, predisposing them to favor coercive action against personalist regimes. This paper presents new quantitative evidence regarding patterns in democratic–personalist conflict and introduces process evidence from US foreign policy decision-making during the Gulf Crisis.